Persuasi Melalui Ilustrasi dalam Iklan Cetak - Didit Widiatmoko Suwardikun (Journal of Visual Art and Design, 2009)
Since our childhood we learn reading as well as writing, but drawing has become something unimportant, until we are often left behind when figuring out what is the meaning and function of a visual image. On the other hand, we are surrounded by visual images which become more increased and more sophisticated, until we are unconsciously affected with many kinds of visual images we perceived. Through observation and visual analysis towards newspaper's printed advertisements within a certain time, it will explain us how the power of illustration, either photography or hand made, is in purpose to get attention and to persuade the target audience. Collaboration between visualization of text messages and visual messages will make the ads more effective.